IMPLEMENTASI PENDEKATAN DIALEKTIS DALAM PENGEMBANGAN METODOLOGI PENDIDIKAN AGAMA ISLAM - Sigit Purwaka (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2020)
Islamic Religious Education subjects taught to students in each level must be treated differently in terms of mindset. If a person is born and develops a process of thinking from the concrete to the abstract or from the simple to the complex then the Islamic Religious Education must also develop following the mindset of students. Islamic Religious Education at the SMA / MA level in formal material can be the same as at the level of SMP / MTs but the ability of students to analyze, find values, and develop their mindset makes Islamic Religious Education subjects feel different. The dialectical approach can be used both by teachers and students. This is done to train the mindset of students and make students better understand an Islamic Religious Education material.